2016
DOI: 10.1002/jssc.201501012
|View full text |Cite
|
Sign up to set email alerts
|

The empirical comparison of cyclofructans and cyclodextrins as chiral selectors in capillary electrophoretic separation of atropisomers of R,S‐1,1’‐binaphthalene‐2,2’‐diyl hydrogen phosphate

Abstract: Native cyclofructans and their isopropyl derivatives were studied as chiral selectors in capillary electrophoresis and compared with α- and β-cyclodextrin. R,S-1,1'-Binaphthalene-2,2'-diyl hydrogen phosphate was used as a model chiral compound. The empirical observation of the enantioselectivity of native cyclofructans and isopropyl derivatives of cyclofructans was described and compared with the cyclodextrins. The influence of methanol and acetonitrile, as the most commonly used organic solvents, and sodium d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In this review, new applications, covering years 2010–2016, are described and discussed with a specific focus on current topics and trends concerning HPLC enantioseparations. Indeed, despite electromigration techniques have been shown to be a powerful tool also for atropisomers separation , HPLC is still the most commonly used technique due to its widespread popularity. At the same time, supercritical fluid chromatography (SFC) has been developed both for analytical and preparative purposes, receiving special attention by pharmaceutical industry and becoming the preferred technique for enantioseparation and purification in drug discovery research.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, new applications, covering years 2010–2016, are described and discussed with a specific focus on current topics and trends concerning HPLC enantioseparations. Indeed, despite electromigration techniques have been shown to be a powerful tool also for atropisomers separation , HPLC is still the most commonly used technique due to its widespread popularity. At the same time, supercritical fluid chromatography (SFC) has been developed both for analytical and preparative purposes, receiving special attention by pharmaceutical industry and becoming the preferred technique for enantioseparation and purification in drug discovery research.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, CFs and CDs have been used as CSs for the separation of BHP . It was observed that for an effective enantioseparation, higher concentrations of CFs were required than of CDs.…”
Section: Chiral Selectorsmentioning
confidence: 99%
“…The macrocyclic oligosaccharides, cyclofructans (CFs), are the next promising chiral selectors for CE. They consist of six or more β‐2,1‐linked D‐fructofuranose units with 18‐crown‐6 ether core . These chiral selectors and their derivatives have been shown to separate a wide range of chiral compounds by HPLC, SFC as well as CE .…”
Section: Introductionmentioning
confidence: 99%